166 Put up with dysgeusia... i don't 'zinc' so!. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - McCormack, Juliet; Curtis, Matthew
Abstract : Background: Taste or gustatory dysfunctions are implicated in loss of appetite, unintended weight loss, malnutrition and reduced quality of life. The benefits of Zinc supplementation for dysgeusia have been documented for the past 20 years with moderate quality supportive evidence available. Improvements in taste have been demonstrated in patients receiving chemoradiotherapy and in those with idiopathic taste loss. However, this approach does not appear to be part of routine practice. Aims: We present a case study of a patient experiencing dysgeusia who was successfully treated with zinc supplementation and lifestyle changes. Case study description: 60 year old patient with a uterine carcinoma receiving Sirolimus treatment. She described extreme taste sensation changes within 1 month of commencing the Sirolimus; foods tasted too salty with an accompanying overwhelming metallic taste. This severely impacted upon her enjoyment of food with reduced appetite, associated weight loss, fatigue and social withdrawal. Physical examination of the oral cavity showed no evidence of infection, ulcers or candidiasis. Zinc supplementation was commenced alongside routine advice including regular oral hygiene, dietary changes and cooking techniques. Results: Specific taste change improvements occurred within 3 weeks with reduction in the salty and metallic tastes. This resulted in improved appetite and tolerance of a wider variety of foods. During subsequent weeks, alongside immunotherapy, there was continued improvement in appetite, enjoyment of eating and quality of life. Conclusion: Although not routine clinical practice, this case demonstrates how inexpensive mineral supplementation can improve dysgeusia and supported tolerance of immunotherapy. Based on this case, we plan to review our palliative care caseload to identify prevalence of this symptom. Our intention would be to then develop an approach to further research this intervention. The research hypothesis is that zinc supplementation plus lifestyle changes is superior to lifestyle changes alone for dysgeusia in palliative care.